The Effect of Image Compression Technique on Wireless Sensor Networks - Aloraib, Alyaa Qusay (Iraqi Journal of Science, 2026)
Recently, wireless multimedia sensor networks (WMSNs) have presented a significant advancement in multimedia applications. However, the transmission of video or images poses unique challenging issues if compared with sending simple signals, due to sensor nodes’ resource limitations, in terms of processing unit specifications, memory, and energy consumption. This research analyzes the effect of transmitting images over low power wireless personal area networks using Internet Protocol version 6 (6LoWPAN), by presenting a new image compression algorithm (AriNib) by utilizing arithmetic coding with a proposed lossy approach that incorporates a modified Niblack thresholding operation to reduce the transmitted image size. As a result, the proposed algorithm lowered the network load and increased its lifetime due to the significant reduction of the consumed energy. AriNib compression algorithm demonstrated efficient image quality with PSNR value about 30 dB, achieving a compression ratio of 2 and a, presenting a promising performance in 6LoWPAN, by reducing transmitting time and consumed energy up to 50% compared to sending the raw image.